Sources and Doses of Phosphorus in the Production of Red-Leaf Lettuce in an Organic Farming System - Tamelini, Bruno Rocha [UNESP]; de Souza, Emanuele Possas [UNESP]; Alves, Thatiane Nepomuceno [UNESP]; Cardoso, Antonio Ismael Inácio [UNESP] (FapUNIFESP (SciELO), 2024)
Lettuce is one of the most consumed vegetables in the world, with significant global economic relevance. Furthermore, the demand for organic products today is considerably higher than in the past, causing changes in the production methods, such as the sources of fertilizer. Several nutrients are limiting for the development of lettuce when deficient in the soil, among them phosphorus stands out. Thus, the purpose of this study was to evaluate the effect of two organic sources of phosphorus at different doses on the production of red-leaf lettuce in an organic farming system. The plants used were from the cultivar Scarlet (Sakata®), transplanted and placed in 12 L plastic pots in a greenhouse, with 10 treatments being carried out in a 2 x 5 factorial scheme. Yoorin Thermophosphate and Bone Meal were tested at doses of 0, 200, 400, 600 and 800 kg ha-1 of P2O5. The experimental design was in randomized blocks, with four replications. Bone Meal resulted in plants with higher dry matter weight and plant circumference but lower values for plant height and leaf width. Doses above the recommended (400 kg ha-1 of P2O5 according to the literature for soils with low phosphorus content: 6 mg dm-3), regardless of the source, resulted in an increase in the values of the characteristics evaluated, but, with a decrease in the increases as high was the dose, except for the number of leaves where the increase was linear. Yoorin Thermophosphate resulted in plants with higher phosphorus content.
Keywords: Lactuca sativa; organic production; phosphate fertilization; yield